Locus Of Control, Penerapan SAP, dan SPI terhadap Kualitas Laporan Keuangan - Siti Salzabila Faizaroh Aizy; Tantina Haryati (Journal of Management and Bussines (JOMB), 2023)
This study aims to prove the influence of Locus of Control (LOC), the application of SAP, and SPI on the quality of financial reports in SKPD Sampang Regency. This research method is quantitative. The population in this study were 25 SKPD in Sampang Regency. The sampling technique used was a purposive sampling technique so that 81 employees met the criteria for respondents. Primary data using a questionnaire used in this study. The analysis technique used is Partial Least Square (PLS) with the help of WarpPls 7.0 software. The results showed that the hypothesis testing was obtained, namely, a) LOC on financial statements has a significant P-Value of 0.005; b) SAP on the financial statements has a significant P-Value of <0.001; c) SPI on financial reports has a significant P-Value of 0.064. Conclusion, LOC and the application of SAP have a significant positive effect on the quality of financial reports. While SPI has no positive effect on the quality of financial reports. Keywords: Quality of Financial Statements, LOC, SAP Implementation, SPI